Technology venture blueprint project name: Swift De' Velvet / Maisarah Abdul Rashid - Abdul Rashid, Maisarah (2020)
My business is called Swift De’Velvet, which is inspired by the swift-style fashion, which is elegant but still perpetuates a charming and captivating modesty. The theme for this boutique is elegant but sweet. This boutique also provide the latest trend for women who wear hijab. My boutique main product is Women Clothes. This boutique is located in Bandar Baru Uda Business Centre in Johor Bahru. This boutique short-term achievement is to be recognized by all people throughout the country. It is certainly not denied that clothing-based commerce faces violent competition in the market today. There are various types of attraction and fashion created to win customer’s taste. Swift De’Velvet need to compete with the slow pace of global-level apparel trade so that this boutique is recognized throughout in the Malaysian population